Metabolic changes after growth hormone treatment in children with growth hormone deficiency and small for gestational age: LG observational study - Kim, Sujin; Kim, Seo Jung; Cho, Kyoung Won; Choi, Youngha; Song, Kyungchul; Lee, Eun Byoul; Chae, Hyun Wook; Suh, Junghwan (Frontiers in Endocrinology, 2025)
PurposeChildren with growth hormone deficiency (GHD) and small for gestational age (SGA) have major growth and metabolic issues. Growth hormone (GH) treatment promotes linear growth and improves metabolic parameters. However, the long-term metabolic effects of this treatment remain unclear. This study aimed to investigate metabolic changes after GH treatment in children with GHD and SGA.MethodsThe study population included 1,788 patients: 1,364 with GHD, 318 with SGA, and 106 with GHD and SGA. Data on growth and metabolic parameters, age, sex, height, weight, body mass index (BMI), and various biochemical markers before and after at least one year of GH treatment were collected from the LG observational study.ResultsGH treatment was initiated at 7.3 ± 2.8 years (GHD: 7.4 ± 2.9 years; SGA: 6.6 ± 2.5 years), with an average treatment duration of 3.8 ± 1.3 years. In the GHD and SGA patient groups, the height and weight standard deviation scores (SDS) significantly increased during treatment. BMI SDS significantly decreased in the first year in both groups; the SGA group showed improvement in years 1–5. AST levels significantly decreased over the 5-year treatment period in both groups. ALT levels significantly decreased in all follow-up years in the GHD group. In both groups, total cholesterol levels decreased and random glucose levels remained within the normal range.ConclusionThese findings demonstrate a positive effect of GH treatment on growth and metabolic parameters in children with GHD and SGA.